Association of Drug Burden Index With Measures of Cognitive Function Among Older Adults. (7th June 2021) - DiNatale, Janie; Crowe-White, Kristi; Ellis, Amy; Douglas, Joy; McDonough, Ian; Yaffe, Kristine
Abstract: Objectives: Many conditions associated with aging result in polypharmacy, and certain medications may impact cognition. One way to assess exposure to such medications is through the use of the drug burden index (DBI)- a validated measure of exposure to anticholinergic and sedative medications, with a higher DBI score indicating a higher drug burden. The objective of this cross-sectional analysis was to investigate the association between DBI and cognitive function assessed by two widely utilized cognitive tests among older adults. Methods: The Health, Aging, and Body Composition Study was a prospective study of community-dwelling adults ages 70–79 years at enrollment. Using baseline data, DBI was calculated by dividing the daily dose of the medication taken by the sum of the daily dose taken and the minimum efficacious dose as approved by the Food and Drug Association. After adjusting for biological sex, race, education, and APOE genotype, the association between DBI and the Digit Symbol Substitution Test (DSST) and Modified Mini-Mental Status Exam (3MS) score was assessed by partial Spearman's rank correlation. Kruskal-Wallis tests were employed to assess significance among DBI scores by tertile. Results: Among those with completed measures ( n  = 790, 52.4% male, 63.3% white), mean scores were as follows: DBI 0.84 ± 0.48, 3MS 90.12 ± 7.9, and DSST 34.7 ± 14.6. Results suggest that DBI was not significantly associated with either 3MS or DSST. However, DBI scores by tertile were significantly associated with DSST scores. Compared to tertile 2, participants in the lowest tertile had significantly lower DBI scores along with significantly higher DSST scores. Mean differences between tertile 1 and 2 were as follows: DBI = 0.1666 and DSST = 3.39. Conclusions: Analyses among the full cohort suggest that DBI was not associated with slower processing speed as assessed by the DSST or with global cognition as assessed by 3MS. Yet with expanded analysis by tertile, results suggest that DBI scores were significantly associated with DSST scores. Future investigations on cognitive function among older adults may benefit from including the DBI analysis by tertile to explain some variance in cognitive test scores. Funding Sources: This is an ancillary analysis, there is no funding applicable.